2020
DOI: 10.1111/sms.13811
|View full text |Cite
|
Sign up to set email alerts
|

Integrating high‐intensity interval training into the workplace: The Work‐HIIT pilot RCT

Abstract: The purpose of this study was to assess the feasibility and preliminary efficacy of a high‐intensity interval training (HIIT) intervention integrated into the workplace on physical and mental health outcomes in a sample of adults. The Work‐HIIT intervention was evaluated at the University of Newcastle (March‐July 2019). University employees (18+ years) who self‐identified as predominantly sedentary at work (n = 47, 43.0 ± 10.7 years; 41 female) were recruited, screened, and randomized after baseline assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(80 citation statements)
references
References 36 publications
10
69
1
Order By: Relevance
“…Notwithstanding any potential adaptations induced by exercise training, to promote long term adherence and compliance, it is essential that interventions are practical and feasible for participants. In the BE@Work trial, mean HIIT session attendance was 83%, which is similar to reported attendance in previous workplace HIIT interventions [range 71% (Eather et al, 2020) to 99% (Allison et al, 2017)]. While high session attendance could indicate sampling bias as discussed subsequently, to promote session attendance in BE@Work, a flexible approach was taken to exercise session attendance; such that 19 group HIIT sessions were conducted each week, with participants asked to attend any three sessions per week.…”
Section: Feasibilitysupporting
confidence: 65%
See 3 more Smart Citations
“…Notwithstanding any potential adaptations induced by exercise training, to promote long term adherence and compliance, it is essential that interventions are practical and feasible for participants. In the BE@Work trial, mean HIIT session attendance was 83%, which is similar to reported attendance in previous workplace HIIT interventions [range 71% (Eather et al, 2020) to 99% (Allison et al, 2017)]. While high session attendance could indicate sampling bias as discussed subsequently, to promote session attendance in BE@Work, a flexible approach was taken to exercise session attendance; such that 19 group HIIT sessions were conducted each week, with participants asked to attend any three sessions per week.…”
Section: Feasibilitysupporting
confidence: 65%
“…While a preliminary body of evidence suggests that workplace HIIT may elicit improvements in markers of physical fitness and cardiometabolic health (Shepherd et al, 2015;Allison et al, 2017;Cuddy et al, 2019;Eather et al, 2020;Metcalfe et al, 2020), most trials to date have been implemented in university workplaces, using a single exercise mode and have not explored participant perceptions of the intervention. To help explore the effectiveness of workplace HIIT further, we undertook a mixed-methods exploratory pilot trial of a workplace HIIT intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delextrat et al [14], found a similar increase in maximum aerobic performance among teenage basketball players after adding 12 HIIT sessions to training during the season. The study by Eather, et al [15], showed significant improvements in aerobic performance after implementing specific high-intensity training with various changes of direction in basketball players. From the literature review it is possible to identify the main problem of our research: there are several training methodologies that fall under the HIIT method, but only some of them have been tested as efficient in basketball, unlike how it happens in other team sports.…”
Section: Introductionmentioning
confidence: 99%